Hot topic or hot air? Climate change and malaria resurgence in East African highlands. - Hay, S; Rogers, D; Randolph, SE; Stern, D; Cox, J; Shanks, G; Snow, R (2002)
Climate has a significant impact on malaria incidence and we have predicted that forecast climate changes might cause some modifications to the present global distribution of malaria close to its present boundaries. However, it is quite another matter to attribute recent resurgences of malaria in the highlands of East Africa to climate change. Analyses of malaria time-series at such sites have shown that malaria incidence has increased in the absence of co-varying changes in climate. We find the widespread increase in resistance of the malaria parasite to drugs and the decrease in vector control activities to be more likely driving forces behind the malaria resurgence.